2021
DOI: 10.1111/tid.13702
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus nephritis in kidney transplant recipients: Epidemiology and outcomes of an uncommon diagnosis

Abstract: Background: Data on epidemiology and outcomes of cytomegalovirus (CMV) nephritis in kidney transplant patients are limited due to the rarity of this condition. Methods:A retrospective review of all kidney transplant recipients (KTR) (n = 6490) and biopsy-proven CMV nephritis between 1/1997 and 12/2020 was performed. Results:The prevalence of CMV nephritis was low: 13/6490 (0.2%). The diagnosis was made at a median of 7.0 months (range 2.6-15.6 months) after transplant. 6 of 13 (46%) patients were CMV (D+/R−). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Most cases were not treated with IV steroids and instead resolved with antiviral treatment. CMV nephritis has been reported post‐kidney transplant but may be difficult to diagnose conclusively due to histologic features overlapping with acute rejection 63–65 . The viral cytopathic effect may not always be seen and were not identified in these cases, 65 and we did not perform PCR to identify whether CMV viral particles were present within the tissue.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Most cases were not treated with IV steroids and instead resolved with antiviral treatment. CMV nephritis has been reported post‐kidney transplant but may be difficult to diagnose conclusively due to histologic features overlapping with acute rejection 63–65 . The viral cytopathic effect may not always be seen and were not identified in these cases, 65 and we did not perform PCR to identify whether CMV viral particles were present within the tissue.…”
Section: Discussionmentioning
confidence: 96%
“…CMV nephritis has been reported post-kidney transplant but may be difficult to diagnose conclusively due to histologic features overlapping with acute rejection. [63][64][65] The viral cytopathic effect may not always be seen and were not identified in these cases, 65 and we did not perform PCR to identify whether CMV viral particles were present within the tissue. Unless there is progressive functional decline, our practice has generally been to defer treatment with steroids until the CMV viremia has resolved.…”
Section: Discussionmentioning
confidence: 99%
“…CMV is commonly presented as a viremia or systemic infection, and direct infection in the kidney allograft is less common than BKV infection [8,65,66]. In the case of CMVassociated nephropathy, pathology shows allograft interstitial inflammation and tubulitis, predominantly with mononuclear cell infiltration (Figure 5) [65].…”
Section: Cytomegalovirus Infectionmentioning
confidence: 99%
“…Characteristics of conditions presenting with interstitial inflammation or cellular infiltrations in the kidney allograft[6,9,13,33,53,66,68,76,78,79].…”
mentioning
confidence: 99%
“…In an Indian cohort, only 10 allograft biopsies out of 2,900 demonstrated CMV nephropathy (including seven for tubulointerstitial nephritis) and the majority of these evolved favorably after antiviral therapy [ 192 ]. A more recent American cohort study reported CMV nephritis prevalence of 0.2% and poorer allograft outcomes [ 193 ]. Typical cytomegalic inclusion bodies (owl’s eye looking) are rarely observed and are usually very focal; they are most often seen in tubular epithelial cells or endothelial cells and rarely in mononuclear inflammatory cells [ 194 , 195 , 196 , 197 ].…”
Section: The Herpesviridae Familymentioning
confidence: 99%